Sphingosine‐1‐Phosphate Receptor 1 Regulates Cardiac Function by Modulating Ca2+ Sensitivity and Na+/H+ Exchange and Mediates Protection by Ischemic Preconditioning. Issue 5 (20th May 2016) - Keul, Petra; van Borren, Marcel M. G. J.; Ghanem, Alexander; Müller, Frank Ulrich; Baartscheer, Antonius; Verkerk, Arie O.; Stümpel, Frank; Schulte, Jan Sebastian; Hamdani, Nazha; Linke, Wolfgang A.; van Loenen, Pieter; Matus, Marek; et al.
Abstract : Background: Sphingosine‐1‐phosphate plays vital roles in cardiomyocyte physiology, myocardial ischemia–reperfusion injury, and ischemic preconditioning. The function of the cardiomyocyte sphingosine‐1‐phosphate receptor 1 (S1P1 ) in vivo is unknown. Methods and Results: Cardiomyocyte‐restricted deletion of S1P1 in mice (S1P1 α MHCC re ) resulted in progressive cardiomyopathy, compromised response to dobutamine, and premature death. Isolated cardiomyocytes from S1P1 α MHCC re mice revealed reduced diastolic and systolic Ca 2+ concentrations that were secondary to reduced intracellular Na + and caused by suppressed activity of the sarcolemmal Na + /H + exchanger NHE‐1 in the absence of S1P1 . This scenario was successfully reproduced in wild‐type cardiomyocytes by pharmacological inhibition of S1P1 or sphingosine kinases. Furthermore, Sarcomere shortening of S1P1 α MHCC re cardiomyocytes was intact, but sarcomere relaxation was attenuated and Ca 2+ sensitivity increased, respectively. This went along with reduced phosphorylation of regulatory myofilament proteins such as myosin light chain 2, myosin‐binding protein C, and troponin I. In addition, S1P1 mediated the inhibitory effect of exogenous sphingosine‐1‐phosphate on β‐adrenergic–induced cardiomyocyte contractility by inhibiting the adenylate cyclase. Furthermore, ischemic precondtioning was abolished in S1P1 α MHCC re mice and was accompanied by defective Akt activation during preconditioning. Conclusions: Tonic S1P1 signaling by endogenous sphingosine‐1‐phosphate contributes to intracellular Ca 2+ homeostasis by maintaining basal NHE‐1 activity and controls simultaneously myofibril Ca 2+ sensitivity through its inhibitory effect on adenylate cyclase. Cardioprotection by ischemic precondtioning depends on intact S1P1 signaling. These key findings on S1P1 functions in cardiac physiology may offer novel therapeutic approaches to cardiac diseases.